Frequency of CYP1A1*2A polymorphisms and deletion of the GSMT1 gene in a Peruvian mestizo population - Angel Tito Alvarado; Ana María Muñoz; María Saravia Bartra; Milton Valderrama-Wong; Daniela González; Luis Abel Quiñones; Nelson Varela; María Rocío Bendezú; Jorge Antonio García; Berta Loja-Herrera (Pensoft Publishers, 2021)
The polymorphic variants of CYP1A1 and the deletion of GSTM1 are present in the Peruvian mestizo population. Wild type and mutated genotypes (WT/*2A and *2A/ *2A) were identified, whose allele frequencies are 0.31 (T allele) and 0.69 (C allele), respectively; 53% with wild type GSTM1 (+) and 47% with null GSTM1. The frequency in Iquiteño emigrants was 0.72 CYP1A1*2A and 25% GSTM1 (-); from Lima 0.67 CYP1A1*2A and 33% of GSTM1 (-). The Hardy-Weinberg equilibrium test for the studied population showed that both frequencies are out of balance, p > .05. The presence of the risk allele of the CYP1A1*2A polymorphism and the deletion in the GSTM1 gene are high, which could be indicative of a phase I and II metabolic imbalance in this group of Peruvian populations, with potential risks of activating agents procarcinogens thus affecting the incidence of tumor pathologies with an environmental component.